Numerical analysis of high-strength reinforcing steel with conventional strength in reinforced concrete beams under monotonic loading - Harba Ibrahim S. I.; Abdulridha Abdulkhalik J.; AL-Shaar Ahmed A. M. (Open Engineering, 2022)
This work presents finite element (FE) modeling using the ABAQUS program to investigate the effect of steel reinforcement with three different types of high-strength steels, grades 420, A1035, and SD685 on the flexural behavior of RC beams under monotonic loading. Experimental findings from the literature have been used to validate the proposed model. The numerical load, deflection, mode of failure, failure concrete strain, and bottom steel strain at failure of 24 numerical specimens with collapsed conditions of tension-controlled, balanced, and compression-controlled are recorded. Also, the effect of compression reinforcement is being investigated. The results reveal that the flexural behavior of the experimental test for the three steel grades is well validated by FE analysis. The ductile and brittle behavior features of yield strength (YS) larger than 420 can be predicted for specimens designed according to current standards ACI-318M-19. Also, the compression reinforcement improves load capacity while reducing displacement. It may be argued that when YS decreases, tensile stress and strain of flexural rebar rise, causing the beam to become more ductile. When the YS increased, the brittle behavior was induced.